The role of metaphors in the development of technologies. The case of the artificial intelligence. (November 2016) - Carbonell, Javier; Sánchez-Esguevillas, Antonio; Carro, Belén
Highlights: Metaphors reigning in society shape the evolution of technologies and the evolution of technologies shape metaphors and how we perceive our daily reality in a two way process. Clash of metaphors conditions the evolution of technologies. CLA offers an interesting framework to analyze metaphors with a future oriented approach and to build scenarios. Abstract: Technology plays a prominent role in configuring the way we live and work. In this paper we go further and think that it is a first level driver in the configuration of our deepest perceptions and has a paramount influence on shaping our worldviews and metaphors, though this aspect goes unnoticed for most of the population. In this paper we analyze how metaphors take action in the characterization of technologies, mainly emerging technologies, and in their evolution, and furthermore the impact of technologies and metaphors on the way we perceive our daily life. We analyze metaphors underlying brain nature and artificial intelligence, raising the connections between them and showing how metaphors in one of these fields impact on the way we understand the other. This fact has important consequences, for instance it conditions the evolution of computational systems, and we propose two scenarios for this evolution. This paper relies on the conceptual model and classification of metaphors proposed by Lakoff and Johnson in "Metaphors we live by", from the orientational metaphors that show values and mantras, to the deepest structural metaphors that are reconfiguring how life is conceived. It also relies on CLA (Causal Layered Analysis) and to its reference book "CLA 2.0" in order to insert this analysis in a wider and future oriented framework and to analyze scenarios.